Tendências e desafios no processo de internacionalização de empresas inovadoras - Henriques, Cátia Andreia Gourgel (2015)
Com a crise económica europeia, e com os crescimentos nacionais baixos ou quase nulos, é fundamental que as empresas portuguesas reforcem a sua presença nos mercados internacionais, para poderem garantir a sua sobrevivência. Os mercados emergentes apresentam oportunidades interessantes na concretização da internacionalização e o envolvimento; Abstract: The European countries are facing a financial crisis and Portugal in particular is having an economic growth close to zero, for this reason, it is become crucial to Portuguese companies increase their presence in international markets, in order to ensure their survival. Emerging markets present interesting opportunities in the process of internationalization for Portuguese firms. Even though the recognition of these markets is recent, acknowledge this fact present great challenge, requiring companies to develop appropriate strategies for successful internationalization. Bearing this in mind, this study addresses the crucial factors for a successful internationalization in emerging markets for innovative companies. The methodology includes document analysis and preparation of a questionnaire that will be presented to four innovative Portuguese companies that have internationalized themselves. The companies chosen for this work are part of the network SME innovation, created by COTEC PORTUGAL, namely: Logoplaste , Vinilconsta , Almadesign and Gatewit .